Knowledge management in sport mega-events: A systematic literature review - Qin, Yuan; Rocha, Claudio M.; Morrow, Stephen (Frontiers in Sports and Active Living, 2022)
The aim of this study was to conduct a systematic review to describe and explore the current state-of-the-art of sport mega-event knowledge management research. Following the PRISMA protocol, the authors conducted a systematic search of academic and grey literature in sport, social sciences, and humanities databases. From the initial 1751 studies reviewed, 16 met the inclusion criteria. In these studies, knowledge management in sport mega-events was mainly researched in the context of the Olympic Games. Most of the studies highlighted the importance of tacit knowledge and specific stakeholders. Social, cultural, and political differences between source and destination weaken the effect of knowledge management, which has become the main issue in the process. Future studies need not only to concentrate on different stakeholders’ needs, but also to have a sound understanding of the social, cultural, political, and historical context of countries/places involved in the transfer process.